Carbon-supported SnO2 nanowire arrays with enhanced lithium storage properties. (10th March 2015) - Yang, Zhenglong; Zhao, Shuping; Jiang, Wei; Sun, Xuelin; Meng, Yanfeng; Sun, Changmei; Ding, Shujiang
Graphical abstract: Carbon-supported SnO2 nanowire arrays were synthesized facilely using self-assembled mesoporous carbon as template followed by partial removal of the carbon. The obtained materials exhibit improved lithium storage capabilities with high capacity retention due to the presence of the carbon buffering layer. Highlights: Carbon-supported SnO2 nanowire arrays were synthesized. No extra carbon coating step is needed. The materials exhibit enhanced lithium storage capacity. Abstract: Carbon-supported SnO2 nanowire arrays were synthesized by a facile strategy using self-assembled mesoporous carbon as template followed by partial removal of the carbon. The as-obtained materials were characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA) and nitrogen adsorption. The resulting products possess a large specific surface area due to the free interspaces between the nanowires. When evaluated as anode materials for lithium-ion batteries, the carbon-supported SnO2 nanowires can deliver large reversible capabilities with excellent cycling performance on account of the mesoporous carbon matrix, which can be served as a buffering layer to relax the stress, reduce the volume variation, and protect the SnO2 nanowires from severe structural degradation during the insertion-deinsertion process of lithium ions.